ETS1 Suppresses Tumorigenesis of Human Breast Cancer via Trans-Activation of Canonical Tumor Suppressor Genes - Kim, Gi-Cheon; Lee, Choong-Gu; Verma, Ravi; Rudra, Dipayan; Kim, Taemook; Kang, Keunsoo; Nam, Jong Hee; Kim, Young; Im, Sin-Hyeog; Kwon, Ho-Keun (Frontiers in Oncology, 2020)
ETS1 has shown dichotomous roles as oncogene and tumor suppressor gene in diverse cancers, but its functionality in breast cancer tumorigenesis still remains unclear. We utilized the Cancer Genome Atlas (TCGA) database to analyze comprehensive functions of ETS1 in human breast cancer (BRCA) patients by investigating its expression patterns and methylation status in relation to clinical prognosis. ETS1 expression was significantly diminished by hyper-methylation on ETS1 promoter region in specimens from BRCA patients compared to healthy control. Moreover, ETS1high BRCA patients showed better prognosis and longer survival compared to ETS1low BRCA patients. Consistent with clinical evidence, comparative transcriptome analysis combined with CRISPR/Cas9 or shRNA based perturbation of ETS1 expression revealed direct as well as indirect mechanisms of ETS1 that hinder tumorigenesis of BRCA cells. Taken together, our study enlightens a novel function of ETS1 as a tumor suppressor in breast cancer cells.